Nurses' collegiality: An evolutionary concept analysis - Kangasniemi, Mari; Rannikko, Sunna; Leino-Kilpi, Helena (United Kingdom, 2025)
Collegiality is one of the fundamental values of the nursing profession. During the nursing history, collegiality has been described as part of a nurse's relationship with their peers and it influences the quality of care they provide and job satisfaction and commitment to their work. Despite earlier definitions, the concept of collegiality in nursing has remained unclear. The aim of this study was to clarify the concept of collegiality in the nursing profession, using Rodger's evolutionary concept analysis. We carried out electronic searches using the CINAHL, PubMed, Scopus, Web of Science, SocINDEX, PsycINFO and Eric databases and manual searches of the reference lists of the selected papers. The searches were limited to peer-reviewed papers published in English language from the inception of database to November 2022. This identified 25 papers. Based on our analysis, the attributes of the concept of collegiality were achieving mutual goals together with equality, reciprocity, trusted advocacy, powerful self-regulation and engaged belongingness. Antecedents of the concept included existing professional group, connection between professionals and professional self-esteem. The consequences were strengthening nurses' professional status, job satisfaction and their ability to provide the best possible patient care. We found that nurses' collegiality was a value-based concept, with a unique character based on professional connections. The concept brought together ethical and pragmatic strategies to achieve the best possible results for the nursing profession. Provided knowledge can be applied for further development of the concept and applying it in clinical research and practice. The concept of nurses' collegiality should also be studied in the future because both the profession and their working environment are constantly changing.